Unravelling pain in diabetic neuropathy patients: Exploring the relationship between perceived pain severity, lifestyle, and coping strategies mediated by self-focused attention and rumination: A cross-sectional study - Fatemeh Hosseini; Amirhossein Yavari; Arya Haddadi (Heliyon)
Objective: Diabetes ranks highly among the world's non-communicable diseases, bringing about a host of physical and psychological impacts on those it afflicts. One such complication is neuropathy, often resulting in significant pain and discomfort. Diabetic neuropathy patients' perceived pain intensity, lifestyle, and pain management strategies measures will be examined in this study. This study also analyses how self-focused attention and rumination mediate this dynamic in Hamedan, Iran, 2023 patients. Methods: The study population comprised neuropathy patients in Hamadan province, Iran. A sample of 253 individuals was selected for the study. Data collection involved several questionnaires: The McGill Pain Questionnaire, Lifestyle Questionnaire, the Coping Strategies Questionnaire, the Self-Focused Attention Questionnaire, and the Rumination Questionnaire. The research model was evaluated using structural equation modeling with AMOS software version 24. Results: Path analysis revealed that the model exploring the relationship between lifestyle-based severity of pain perception and pain coping strategies, mediated by self-focused attention and rumination, was a good fit for patients with diabetic neuropathy. (P < 0.05) Conclusion: The findings suggest that an improved lifestyle and more effective pain management strategies are linked to decreased severity of pain perception in patients with diabetic neuropathy. Additionally, the research indicates that self-focused attention and high levels of rumination may lead to increased severity of pain perception in these individuals. This research has the potential to advance the understanding of diabetic neuropathy's underlying mechanisms and enhance treatment approaches, ultimately playing a significant role in improving the quality of life for these patients.